2015
DOI: 10.1139/cjp-2015-0093
|View full text |Cite
|
Sign up to set email alerts
|

R-matrix calculations of photoionization cross section of Ne-like tungsten

Abstract: The photoionization cross section calculation for the ground state 1s 2 2s 2 2p 6 1 S (J = 0) of Ne-like W 64+ has been performed in the close-coupling approximation using the Dirac-Coulomb R-matrix method. The resonance structures are analysed and described by finding the resonance energy positions of prominent Rydberg series 2s2p 6 ( 2 S)np 1 P 0 for W LXV ion. To calculate fine structure energy levels, multi-configuration Dirac-Fock and relativistic distorted-wave methods have been employed. Wherever possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…After this, several x-ray lines were precisely measured using EBIT [20][21][22]. Recently, Khatri et al [23] calculated photoioization cross section of Ne-like tungsten using R-matrix method. More recently, Aggarwal and keenan [24] calculated energy levels and radiative rates for 121 levels of W LXV.…”
Section: Introductionmentioning
confidence: 99%
“…After this, several x-ray lines were precisely measured using EBIT [20][21][22]. Recently, Khatri et al [23] calculated photoioization cross section of Ne-like tungsten using R-matrix method. More recently, Aggarwal and keenan [24] calculated energy levels and radiative rates for 121 levels of W LXV.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, this kind of resonance peak is very narrow and the corresponding Rydberg resonance series converges quickly to its excitation threshold [58]. From a theoretical point of view, the overlap of these resonant peaks is caused by a relativistic intermixing and coupling of the included channels [39]. It is also found that the resonant peaks beyond the energy 1277.42 Ryd become extremely weak and, hence, further calculations for higher photoionizing energies are not performed in this work.…”
Section: Resultsmentioning
confidence: 93%
“…López et al theoretically studied the direct photoionization of W 63+ and W 64+ ions using a combination of the perturbative dipolar approach and the Sturmian model [38]. Moreover, the photoionization of W 64+ ions was also studied using the Dirac-Coulomb R-matrix method [39].…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy of the method depends on the number of configurations required to achieve a desired accuracy. We have also applied this method in our previous work [64][65][66][67][68][69][70][71][72][73][74]. In Table 1 Table 1-3, one can see that the contribution of Breit and QED corrections are equal in the order of 10 -2 for all levels except level number 3 and 27.…”
Section: Energy Levelsmentioning
confidence: 92%
“…To execute accurate and elaborate calculations, we have chosen a fully relativistic MCDF method which was improved by Norrington [62] formerly built by Grant et al [63] and has been successfully implemented in our previous work [64][65][66][67][68][69][70][71][72][73][74]. QED corrections and Breit corrections are taken as a first order perturbation theory.…”
Section: Theoretical Methodsmentioning
confidence: 99%